Rectosigmoid Cancer—Rectal Cancer or Sigmoid Cancer?. (18th August 2022) - Hui, Caressa; Baclay, Richel; Liu, Kevin; Sandhu, Navjot; Loo, Phoebe; von Eyben, Rie; Chen, Chris; Sheth, Vipul; Vitzthum, Lucas; Chang, Daniel; Pollom, Erqi
Abstract : Objectives: We aimed to determine the optimal treatment for patients with locally advanced rectosigmoid cancers, and to determine whether this can be guided by distance from anal verge (AV) and/or anatomic landmarks such as the sacral promontory and peritoneal reflection (PR). Materials and Methods: We retrospectively reviewed patients with T3-T4 and/or node-positive rectosigmoid cancers who underwent surgery from 2006 to 2018 with available pelvic imaging. We included tumors at 9 to 20 cm from the AV on either staging imaging, or colonoscopy. Patients were stratified into those who received neoadjuvant therapy, and those who underwent upfront surgery. Comparisons of characteristics were performed using χ 2 test and Fischer exact test. Locoregional failure (LRF) and overall survival were compared using Cox regressions and Kaplan-Meier analysis. Results: One hundred sixty-one patients were included. Ninety-seven patients had neoadjuvant therapy, and 64 patients had upfront surgery. Median follow-up time was 45.1 months. Patients who had neoadjuvant therapy had tumors that were higher cT stage ( P <0.01) with more positive/close circumferential resection margins seen on imaging by radiologists (28.9% vs. 1.6%, P =0.015). The 2-year rate of LRF, distant metastases, or overall survival was not significantly different between the 2 groups. None of 15 patients with tumors below the PR treated with neoadjuvant therapy had LRF, but 1 (25%) of 4 patients with tumors below the PR treated with adjuvant therapy experienced LRF ( P =0.05). Conclusions: Patients with tumors below the PR may benefit more from neoadjuvant therapy. The PR on imaging may be a reliable landmark in addition to the distance from the AV to determine the most appropriate treatment option.